2012
DOI: 10.1016/j.expneurol.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function following bilateral mid-cervical contusion injury in the adult rat

Abstract: The consequences of spinal cord injury (SCI) are often viewed as the result of white matter damage. However, injuries occurring at any spinal level, especially in cervical and lumbar enlargement regions, also entail segmental neuronal loss. Yet, the contributions of gray matter injury and plasticity to functional outcomes are poorly understood. The present study addressed this issue by investigating changes in respiratory function following bilateral C3/C4 contusion injuries at the level of the phoenix motoneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 99 publications
10
102
1
Order By: Relevance
“…Previously developed contusion injuries at mid-cervical levels in rodents have also been associated with respiratory complications. 6,23 Interestingly, the C5 impact was almost never associated with mortality in the present study, suggesting a greater susceptibility of overall ventilation to contusion injury at the C4 region. Preliminary data from our laboratory showed that generation of a single impact at the C4 level only was sufficient to obtain long-lasting deficits in ipsilateral hemi-diaphragm function (not shown); however, the double C4 + C5 injury paradigm resulted in significantly greater functional compromise.…”
Section: Figcontrasting
confidence: 43%
See 2 more Smart Citations
“…Previously developed contusion injuries at mid-cervical levels in rodents have also been associated with respiratory complications. 6,23 Interestingly, the C5 impact was almost never associated with mortality in the present study, suggesting a greater susceptibility of overall ventilation to contusion injury at the C4 region. Preliminary data from our laboratory showed that generation of a single impact at the C4 level only was sufficient to obtain long-lasting deficits in ipsilateral hemi-diaphragm function (not shown); however, the double C4 + C5 injury paradigm resulted in significantly greater functional compromise.…”
Section: Figcontrasting
confidence: 43%
“…Several contusion models at mid-cervical levels (C3, C4, C5) that show chronic abnormalities in respiratory parameters have been developed in the rat. [22][23][24][25] The extension of a contusion injury model to the mouse provides opportunities for manipulating genes of interest and for evaluating their role in relevant outcome measures affected by cervical spinal contusion such as forelimb motor function, respiratory function, and neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more clinically relevant animal model is a contusive injury at the cervical level [26][27][28] . However, the reproducibility of the injury is inconsistent, mainly due to the location of the descending respiratory pathways and the impossibility to do an extensive contusion (which will drastically reduce the survival rate of the animals).…”
Section: Benefits Of Using a Rat Model Of C2 Injury To Study Respiratmentioning
confidence: 99%
“…The majority of these injuries affect mid-cervical levels (Shanmuganathan et al, 2008) (the location of the PhMN pool), and respiratory function following mid-cervical SCI is significantly determined by PhMN loss/sparing (Strakowski et al, 2007). Although use of thoracic models has predominated, cervical SCI animal models have recently been developed (Aguilar and Steward, 2010; Awad et al, 2013; Gensel et al, 2006; Lane et al, 2012; Lee et al, 2010; Sandrow-Feinberg et al, 2009; Sandrow-Feinberg et al, 2010; Sandrow et al, 2008; Stamegna et al, 2011), including our own (Nicaise et al, 2012). Because of the relevance of astrocyte and GLT1 dysfunction to PhMN loss/injury following cervical trauma, we targeted transplantation in the present study to cervical spinal cord ventral horn in a cervical contusion SCI model.…”
Section: Introductionmentioning
confidence: 99%